A Comparison of Clinical Parameters and Outcomes over 1 Year in Home Hemodialysis Patients Using 2008K@home or NxStage System One. Issue 2 (March 2016) - Brunelli, Steven M.; Wilson, Steven M.; Ficociello, Linda H.; Mullon, Claudy; Diaz-Buxo, Jose A.
Abstract : The prevalence of home hemodialysis (HHD) in the United States is growing, driven in part by improvements in dialysis machines for home use. We assessed clinical parameters and outcomes in HHD patients using either Fresenius 2008K@home or NxStage System One over 1 year. Patients were 18 years or older and received HHD for ≥30 days between January 1, 2009, and June 30, 2010. A propensity score match was used to control for differences in baseline characteristics, and 2008K@home patients were stratified by frequency of use. Data for outcome measures were analyzed using generalized linear mixed models. Treatment frequency was lower for 2008K@home groups than System One. Mean standardized Kt/V (stdKt/V) was 2.75 for 2008K@home ≥3.5x/week users and 1.99 for System One users ( p < 0.001). Erythropoiesis-stimulating agent use tended to be lower for patients using System One. There were no statistically significant differences across groups in serum albumin, calcium, phosphorus, hemoglobin, or parathyroid hormone levels, normalized protein catabolic rate, body mass index, number of hospitalizations, or hospitalized days. Clinical parameters and outcomes for HHD patients using 2008K@home and System One were largely equivalent, although 2008K@home use was associated with higher stdKt/V. Further studies will be required to establish whether these differences in stdKt/V relate to differences in technology, treatment schedule, or a combination thereof. Abstract : Supplemental Digital Content is available in the text.